Number of Nodules, Child-Pugh Status, Margin Positivity, and Microvascular Invasion, but not Tumor Size, are Prognostic Factors of Survival after Liver Resection for Multifocal Hepatocellular Carcinoma - Goh, B.K.P. (2016)
10.1007/s11605-014-2542-0